2021
DOI: 10.21203/rs.3.rs-990513/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Ellagic Acid, Cilostazol and Their Combination on Amikacin Induced Nephrotoxicity in Rats

Abstract: Amikacin(AK) has the largest spectrum of aminoglycosides. However, its use is limited due to nephrotoxicity and ototoxicity. Ellagic acid (EA) is a plant phenolic structure. it has antioxidant, anticarcinogenic and antimutagenic properities. Cilostazol (CTZ) is a PDE Ш inhibitor, it is a potent vasodilator and antiplatelet drug. This study aimed to determine if EA and cilostazol have a protective effect against nephrotoxicity caused AK. Forty nine rats were divided into seven equal groups: control normal; AK 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…In the study conducted by Pradiba Amadita et al, it was found that (73.3%) of the subjects suffer from cardiomegaly and (26.7%) do not show a picture of cardiomegaly in CXR. This concludes the majority of the subjects had cardiomegaly and CKD is significantly correlated with the incidence of cardiomegaly [11,12]. From the Comparison between radiologist 1 and radiologist 2 in terms of disease diagnosis, we concluded that the level of agreement in pneumonia (29.6%), pulmonary edema (25.0%), pleural effusion (28.6%) and cardiomegaly (20.0%).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the study conducted by Pradiba Amadita et al, it was found that (73.3%) of the subjects suffer from cardiomegaly and (26.7%) do not show a picture of cardiomegaly in CXR. This concludes the majority of the subjects had cardiomegaly and CKD is significantly correlated with the incidence of cardiomegaly [11,12]. From the Comparison between radiologist 1 and radiologist 2 in terms of disease diagnosis, we concluded that the level of agreement in pneumonia (29.6%), pulmonary edema (25.0%), pleural effusion (28.6%) and cardiomegaly (20.0%).…”
Section: Discussionmentioning
confidence: 80%
“…The data obtained from this study was analyzed using Libyan J Med Res. 202317-2 (8)(9)(10)(11)(12)(13)(14)(15)(16) the chi-square test in the SPSS statistical package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation